Italy, 1000-1400 - Arkomanis, Ektoras (Bloomsbury, 2019)
This chapter - part of a two-volume work about architectural history - covers Italian architecture from 1000 BCE to 1400 BCE. Political, economic and military influence was exercised on the Italian Peninsula, at one time or other, by the Holy Roman Empire and the House of Hohenstaufen, the Normans, the Lombard and Tuscan city-states, the Papal States, the Kingdom of Sicily, the ever-weakening Byzantine Empire and the gradually retreating Saracens. Alliances were formed and broken continually, and boundaries shifted, so the zones of influence present a rich and complex history with plenty of geographical and temporal overlaps. Civilizations flourished not only during intervals of peace, but also amidst the harshest of conflicts. Perhaps the most telling evidence of determination is that so many public works were continued or completed even after the bubonic plague, or ‘Black Death’, which reached Italy in 1347 and purportedly eliminated between a third and half of the peninsula’s population. In the centuries that followed the Carolingian Renaissance (late eighth to late ninth centuries; see Chapter 32) the city of Rome itself faced harsh economic and political realities. These were hard to reconcile to the collective consciousness of its past grandeur. In the twelfth century the city underwent a renewal, reflected in its form and monuments. Its capabilities were improved and so in the 1300s reality began to correspond again with the perpetual aspirations to greatness.